Pengaruh Kreativitas dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Melalui Motivasi Berwirausaha Pada Santri dan Santriwati Pondok Pesantren Ad-Daraaen Makassar - Andika Isma; Muhammad Rakib; Rusni Andriani; Ina Septiani (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2023)
Entrepreneurship is a creative ability, interest, and motivation. keen to see opportunities and always open to any input and positive changes that can keep the business growing. Business should have value and be useful. The purpose of this research is to explore creativity, interest, and motivation in entrepreneurship in Islamic boarding schools, as well as to support Islamic spiritual education in entrepreneurship education. This research is a quantitative research using a data processing approach for Islamic boarding schools in exploring the entrepreneurial process through education at Islamic boarding schools. In this study, data collection used a questionnaire filling technique by sending it to Islamic boarding schools, observing and studying documents. The results of the study show that entrepreneurship is internalized in Islamic boarding schools through religious and entrepreneurial values based on Worship (worship to Allah SWT) and Khidmah (piety to humanity), where all business and economic activities carried out aim to worship Allah SWT. and for the benefit of society.